ECG dispersion mapping on CardioVisor-06 C in outpatient setting - Ol'ga Ivanovna Evstigneeva; Iraida Anatol'evna Safiulova; O I Evstigneeva; I A Safiulova (Терапевтический архив, 2011)
Aim. To evaluate diagnostic potential of measurement of myocardial metabolism with ECG dispersion mapping based on low-amplitude (10-30 mcV) oscillations of the electrocardiographic signal in persons aged 30-80 in health and pathology. Material and methods. A total of 283 patients were examined. The input ECG signal was digitized isolating 15 successive complexes for 30-60 s with reference to results of the analysis of ECG signal low amplitude oscillation amplitude dispersions, the data were processed on the weak signal multiplication module, the surface map of electric fluctuations formed at output was projected on the surface of 3D anatomic model of the heart. Results. Age groups were the following: 30-40 years (n = 18, 6.4%), 41-50 years (n = 68, 24%), 51-60 years (n = 90, 31.8%), 61-70 years (n = 78, 27.6%), 71 and older (n = 29, 10.2%). According to the integral index of myocardial changes the patients were divided into 4 groups: group 1 (n = 182) - up to 15% (normal), group 2 (n = 83) - 16-30% (moderate changes), group 3 (n = 16, 5.6%) - 31-45% (marked changes), group 4 (n = 2) - over 45% (dramatic changes). The examination aimed at not only early detection of pathology in healthy able to work population, but also at drawing attention of this population to health protection programs. Conclusion. Myocardial metabolism disorders were detected in 64 patients, borderline conditions of the myocardium were detected in 86 patients. Almost 50% of able to work examinees aged 50 years and younger have borderline conditions, older patients have these conditions in 30-35%. Thus, older population pay more attention to their health.